Brake disc with nickel-free steel layer and method for producing the same
A nickel-free steel base layer with a carbide surface coating on brake discs enhances mechanical strength and reduces nickel release, overcoming wear and oxidation challenges in conventional brake discs.
Patent Information
- Application Number
- JP2024538145
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-23
- Filing Date
- 2022-12-13
- Publication Date
- 2025-01-17
AI Technical Summary
Conventional brake discs made of gray cast iron or steel suffer from excessive wear, surface oxidation leading to rust, and protective coatings used to mitigate these issues often flake off, releasing nickel particles that can cause sensitization and are resource-intensive.
A brake disc composed of a nickel-free steel base layer with a surface protective coating containing carbides, such as tungsten carbide or chromium carbide, applied using high kinetic energy impact deposition techniques, ensuring adequate mechanical strength and reduced nickel release.
The solution provides a brake disc with reduced nickel emission, improved mechanical performance, and lower resource consumption while maintaining thermal and mechanical integrity, addressing the issues of wear and oxidation.
Smart Images

Figure 2025501123000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a brake disc and a brake disc for a disc brake. [Background technology]
[0002] The brake disc of a vehicle disc brake system consists of an annular structure, i.e. a brake band, and a central fixed element, known as a bell, by which the disc is fixed to a rotating part of the vehicle suspension, e.g. a hub. The brake band is provided with opposing braking surfaces suitable for cooperating with friction elements (brake pads) housed in at least one caliper body arranged astride such brake band and integrated with a non-rotating part of the vehicle suspension. The controlled interaction between the opposing brake pads and the contrasting braking surfaces of the brake band provides, by friction, a braking action that allows the vehicle to slow down or stop.
[0003] Brake discs are generally made from grey cast iron or steel. This material provides good braking performance (especially reduced wear) at a relatively low cost. Discs made from carbon or carbo-ceramic materials offer much higher performance but at a much higher cost.
[0004] The limitations of conventional discs made of cast iron or steel are related to excessive wear. With regard to discs made of grey cast iron, another very negative aspect is related to the excessive surface oxidation that leads to the formation of rust. This aspect affects both the performance and the appearance of the brake disc, since rust on the brake disc is aesthetically unacceptable to the user. To address such problems, attempts have been made to provide protective coatings on grey cast iron or steel discs. The protective coatings serve, on the one hand, to reduce the wear of the disc and, on the other hand, to protect the grey cast iron base from surface oxidation, thereby preventing the formation of a layer of rust. However, the protective coatings currently available and applied to discs, while providing wear resistance, are also responsible for flaking that causes detachment from the disc itself.
[0005] A protective coating of this kind is described, for example, in US Patent No. 4,715,486 for low wear disc brakes. In particular, cast iron discs have a coating consisting of a particulate material deposited on the disc by high kinetic energy impact techniques. According to a first embodiment, the coating comprises a mixture of 20% to 30% tungsten carbide, 5% nickel and the balance chromium and tungsten carbide.
[0006] In the case of application of coatings by flame spray technology, the cause of peeling of conventional protective coatings from discs made of aluminum or aluminum alloys is the presence of free carbon in the protective coating. Such a phenomenon also affects discs made of gray cast iron or steel.
[0007] A solution to the aforementioned problem has been proposed by the same applicant in international application WO2014 / 097187 for discs made of grey cast iron or steel. It consists in making a protective coating on the braking surface of the disc brake, obtained by depositing a particulate material consisting of 70-95% by weight of tungsten carbide, 5-15% by weight of cobalt and 1-10% by weight of chromium. The deposition of the particulate material is obtained by HVOF (High-Velocity Oxygen Fuel) or HVAF (High-Velocity Air Fuel) or KM (Kinetic Metallization) techniques.
[0008] More specifically, the solution provided in WO 2014 / 097187 allows the combination of HVOF, HVAF or KM deposition techniques with the chemical components used to form the coating to obtain a protective coating with high bond strength that ensures a high degree of fixation to the grey cast iron or steel. The aforementioned solution allows the phenomenon of peeling of the protective coating observed in the previously known techniques to be significantly reduced, but not completely eliminated. In fact, peeling and sagging of the protective coating still occur in disks with a protective coating produced according to WO 2014 / 097186, although less frequently than in the previously known techniques.
[0009] The aforementioned peeling and sagging may in particular contribute to the release by friction of nickel particles, this metal contributing significantly to the sensitization phenomenon in the population.
[0010] However, in the specific field of the manufacture of steel for brake discs, the presence of nickel is considered to be essential to this day, since it increases the strength and toughness of the steel. In addition, nickel improves the oxidation and corrosion resistance of the steel, but more importantly, nickel improves the wear and heat resistance of the steel. Therefore, to this day, the presence of nickel has been considered an essential element in the manufacture of brake discs made of cast iron or steel.
[0011] However, taking into account simultaneously the advantages in terms of wear resistance ensured by the protective coating and the need to maintain the presence of nickel in the composition of the brake disc, a need is felt in the art to overcome the drawbacks mentioned above with reference to the prior art.
[0012] In particular, a need is felt for grey cast iron or steel discs which are able to reduce the release of nickel particles and at the same time ensure adequate or equivalent thermal and mechanical performance typical of prior art brake discs, including high resistance to disc wear and reliability over time.
[0013] According to a further aspect, a need is also felt to produce steel discs with less resource consumption (and therefore also at a lower cost) while maintaining adequate coating hardness and at the same time reducing (or eliminating) the release of nickel particles. Summary of the Invention
[0014] The need for a brake disc which can reduce the release of nickel particles while at the same time ensuring adequate or equivalent thermal and mechanical performance is met by a brake disc and a method for manufacturing a brake disc according to the attached independent claims. [Brief description of the drawings]
[0015] Further characteristics and advantages of the present invention will be better understood from the following description of preferred embodiments thereof, given by way of non-limiting example: [Figure 1] FIG. 1 is a plan view of a disc brake according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of the disk of FIG. 1 taken along line II-II shown therein, according to an embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view of the disk of FIG. 1 taken along the line II-II shown therein, according to a further embodiment of the invention. [Figure 4]FIG. 4 is a cross-sectional view of one half of a brake band according to an embodiment of the present invention. [Diagram 5] FIG. 5 is a cross-sectional view of half of a braking band according to a second embodiment of the present invention. [Figure 6] FIG. 6 is a cross-sectional view of a half of a brake band according to a third embodiment of the present invention. [Figure 7] FIG. 7 is a cross-sectional view of half of a braking band according to a fourth embodiment of the present invention. [Figure 8] FIG. 8 is a cross-sectional view of half of a braking band according to a fifth embodiment of the present invention. [Figure 9] FIG. 9 is a cross-sectional view of a half portion of a braking band according to a sixth embodiment of the present invention. [Figure 10] FIG. 10 is a cross-sectional view of one half of a braking band according to a seventh embodiment of the present invention.
[0016] Elements or parts of elements that are common to the embodiments described below are designated by the same reference numerals. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] With reference to the aforementioned figures, the reference numeral 1 generally indicates a brake disc according to the invention.
[0018] In this disclosure, where numerical percentage ranges are given, it is understood that the extremes of such ranges are always constituted, unless otherwise specified.
[0019] According to a general embodiment of the invention shown in the accompanying drawings, a brake disc 1 consists of a braking band 2 with two opposing braking surfaces 2a and 2b, each braking surface 2a and 2b at least partially defining one of the two main surfaces of the disc.
[0020] The brake band 2 is made of grey cast iron or steel.
[0021] Preferably, the brake band 2 is made of grey cast iron. In particular, the entire disc is made of grey cast iron. In the following description, therefore, reference is made to a disc made of grey cast iron, without excluding the possibility of it being made of steel.
[0022] The disc 1 comprises a base layer 30 which covers at least one of the two braking surfaces 2a, 2b of the braking band and which is preferably in direct contact with such braking surface 2a, 2b.
[0023] According to one embodiment of the invention, such base layer 30 is made of steel with a nickel content lower than or at most equal to 15%.
[0024] According to a further aspect of the invention, such base layer 30 is made of steel having a nickel content lower than or at most equal to 7.5%, and even more preferably lower than or at most equal to 5%.
[0025] According to a further aspect of the invention, such base layer 30 is completely nickel-free, which makes it possible to limit, if not avoid, the dispersion of nickel particles during the service life of the brake disc 1.
[0026] Generally, in this disclosure, when reference is made to expressions such as "nickel-free" or "nickel-free", it means that it does not contain any nickel, but also that it does not contain nickel minus small amounts of nickel that may be present due to residual traces or impurities resulting from the manufacturing steps, but still, the amount of nickel for any layer is less than 1%, and in some cases, at most strictly less than 5%.
[0027] Furthermore, according to the invention, the steel of the base layer 30 is composed of 10%-15% chromium Cr, at most 1% silicon Si, at most 4% manganese Mn, 0.16%-0.5% carbon C and the balance iron Fe, i.e. the remaining percentage by weight iron, which allows the production of a nickel-free martensitic steel.
[0028] Preferably, the carbon content of the base steel is comprised between 0.16-0.25%.
[0029] Moreover, in a highly advantageous manner, said composition makes it possible to use a small proportion of carbides that may be contained in the steel, without reducing the possible hardness of the coating (as will be explained in more detail later in the text).
[0030] According to a preferred variant, the chromium (Cr) content in the steel of the base layer 30 is comprised between 11% and 14%, including the extremes.
[0031] It is clear that a person skilled in the art knows what is meant when referring to the nickel content or percentage of other components of a steel alloy or cast iron. For example, it is common to refer to the content in mass % relative to the total content of the alloy. Thus, in the remainder of this disclosure, specific calculations of percentages are specified only in cases where they deviate from the above definitions, and when not specified, the indicated percentages should be considered as understood by a person skilled in the art.
[0032] According to a variant of the invention, such as that shown in Figure 5, the base layer 30 also consists of one or more carbides contained in nickel-free steel, said inclusion being achieved by techniques known to those skilled in the art for the inclusion of carbides in steel, for example the carbides being dissolved in the alloy.
[0033] Preferably, the one or more contained carbides comprise at least one carbide selected from the group consisting of tungsten carbide (WC), chromium carbide (preferably, but not limited to, Cr3C2), niobium carbide (NbC), titanium carbide (TiC). It is clear that one or more carbides may be present and may be selected from the aforementioned group, or all of the carbides in this group may be present.
[0034] The one or more included carbides comprise at least one carbide selected from the group consisting of tungsten carbide (WC), chromium carbide (eg, Cr3C2), niobium carbide (NbC), and titanium carbide (TiC).
[0035] According to an advantageous embodiment, for example as shown in Fig. 6, the brake disc 1 comprises a protective coating 3 covering a base layer 30 at least on one side of the two braking surfaces 2a, 2b of the braking band. Such a protective coating 3 is provided on the side of the base layer 30 not facing the braking surfaces 2a, 2b. Furthermore, the protective coating 3 is applied by thermal spray deposition techniques, for example by HVOF (High-Velocity Oxy-Fuel) technology or by HVAF (High-Velocity Air Fuel) technology, also by HAAPS (Atmosphere Plasma Spray) technology, or by cold spray deposition techniques, for example KM (Kinetic Metallization) technology, or by laser beam deposition techniques, for example LMD (Laser Metal Deposition) technology, or HSLC (High Speed Laser Cladding) technology, or EHLA (Extreme High Speed Laser Application) technology, or TSC (Top Speed Cladding) technology.
[0036] The protective surface coating 3 is thus obtained by depositing one or more carbides in particulate form, preferably tungsten carbide (WC) or chromium carbide (for example Cr3C2) or niobium carbide (NbC) or titanium carbide (TiC), directly on the disk 1 by the HVOF technique, or the HVAF (High-Velocity Air Fuel) technique, or also the KM (Kinetic Metallization) technique.
[0037] According to a further variant, the protective surface coating 3 is made of a steel with a nickel content of less than or equal to 15%, or at most less than or equal to 7.5%, or at most less than or equal to 5%, or even more preferably completely nickel-free, and one or more carbides contained in the steel. In this variant, in other words, on the cast iron strip, a base layer 30 made of nickel-free steel and on the base layer 30, a protective surface coating 3 made of said steel and one or more carbides contained in the steel are bonded in a given order.
[0038] The presence of carbides deposited on the surface of or contained in a substantially or completely nickel-free steel can impart adequate mechanical strength and wear resistance to compensate for the deficiency or complete lack of nickel in the steel.
[0039] According to a variant, the surface protective coating 3 is composed of one or more of the following carbides: tungsten carbide (WC), niobium carbide (NbC), chromium carbide (for example Cr3C2), titanium carbide (TiC). Preferably, such a surface protective coating 3 is formed by a thermal spray deposition technique, for example the High-Velocity Oxy-Fuel (HVOF) technique, or the High-Velocity Air Fuel (HVAF) technique, or the Atmosphere Plasma Spray (APS) technique, or a cold spray deposition technique, for example the Kinetic Metallization (KM) technique, a laser beam deposition technique, for example the Laser Metal Deposition (LMD) technique, the High-Speed Laser Cladding (HSLC) technique, the Extreme High-Speed Laser Application (EHLA) technique, or the Top Speed Cladding (TSC) technique. It is therefore clear that there may be several carbides selected from the aforementioned group, or all the carbides present in this group.
[0040] According to an advantageous embodiment, the surface protective coating 3 is composed of chromium carbide (eg Cr3C2) and titanium carbide (TiC).
[0041] According to a variant, the surface protective coating 3 consists of at least one metal oxide or a mixture of metal oxides or a mixture of metal and ceramic material, preferably a mixture of Al2O3 aluminum oxide or a mixture of Al2O3 and an Fe-Cr intermetallic matrix, for example Fe28Cr.
[0042] According to an advantageous variant, the protective surface coating 3 is made up of one or more of the following carbides: tungsten carbide (WC), niobium carbide (NbC), chromium carbide (e.g. Cr3C2), titanium carbide (TiC), with a mixture of metal oxides or with a mixture of metal and ceramic material, preferably with aluminum oxide Al2O3 or with an intermetallic matrix Fe-Cr, for example Fe28Cr.
[0043] It will be appreciated that the above oxides or mixtures of oxides, or mixtures of metals or metals and ceramic materials, or mixtures of carbides and metal oxides are preferably deposited by the same particle form carbide deposition techniques as described above and in the present disclosure.
[0044] Preferably, the thickness of the surface protective coating 3 is 30 μm-150 μm, preferably 50 μm-90 μm.
[0045] Preferably, the steel of the base layer 30 further comprises up to 4% manganese (Mn) to at least partially compensate for the deficiencies in steel alloy properties typically imparted by the presence of nickel and to increase mechanical strength, and more preferably the manganese content is between 0.5-4%, including the extremes.
[0046] Preferably, the thickness of the base layer 30 is comprised between 20 μm and 300 μm, preferably equal to 90 μm.
[0047] According to a variant of the invention, to compensate for the low or complete absence of nickel and to obtain sufficient performance as a brake disc, the steel of the base layer 30 has, in the extremes, a molybdenum content of 0.5%-10%, more preferably 0.5%-4.5%, and a manganese content of 0.5%-5%. The presence of molybdenum and manganese in the aforementioned proportions allows to obtain sufficient mechanical strength at the same time as sufficient corrosion resistance.
[0048] According to an embodiment, an intermediate layer 300 of nickel-free steel is interposed between the base layer 30 and at least one of the two braking surfaces 2 a, 2 b of the braking band 2 .
[0049] According to an embodiment, the intermediate layer 300 is made of nickel-free steel with 10%-15% chromium (Cr), at most 1% silicon (Si), at most 4% manganese (Mn), 0.16%-0.5% carbon (C), and the balance iron (Fe). Preferably, the carbon (C) content is 0.16% to 0.25%.
[0050] According to a variant, between the base layer 30 and at least one of the two braking surfaces 2a, 2b of the brake band 2 an intermediate layer 300 of steel made of nickel is interposed, preferably having a nickel content of more than 5% if the base layer 30 is completely nickel-free, more preferably having a nickel content at least equal to 5%, and even more preferably having a nickel content at least equal to 5% and lower than 15%.
[0051] According to an embodiment, the intermediate layer 300 consists of steel with a nickel content at most equal to 15%.
[0052] According to an embodiment, the intermediate layer 300 consists of steel with a nickel content of at most or equal to 7.5%.
[0053] The presence of intermediate layer 300, thanks to the presence of base layer 30, makes it possible to obtain a disc with adequate mechanical characteristics and at the same time with a reduced environmental impact.
[0054] According to one embodiment, the intermediate layer 300 is made of steel with 10%-15% chromium (Cr), at most 1% silicon (Si), at most 4% manganese (Mn), 0.16%-0.5% carbon (C) and the remainder iron (Fe). Preferably, the carbon content (C) of the steel of the intermediate layer 300 is between 0.16% and 0.25%, without including the extremes.
[0055] According to one embodiment, the surface protective coating 3 consists of a steel consisting of 10%-15% chromium (Cr), at most 1% silicon (Si), at most 4% manganese (Mn), 0.16%-0.5% carbon (C) and the remainder iron (Fe), preferably without nickel.
[0056] Preferably, the carbon content (0C) of the coated steel is 0.16%-0.25%, not including the extremes.
[0057] According to an embodiment, an auxiliary ferrite-nitrocarburized or ferroaluminate layer is interposed between one of the two braking surfaces 2a, 2b of the braking band and the base layer 30, or between one of the two braking surfaces 2a, 2b of the braking band and the intermediate layer 300, or between the base layer 30 and the surface protective coating 3, or between the intermediate layer 300 and the base layer 30.
[0058] According to an embodiment, an auxiliary ferrite-nitrocarburizing layer or an auxiliary ferroaluminate layer is interposed between one of the two braking surfaces 2a, 2b of the brake band and the base layer 30, or between one of the two braking surfaces 2a, 2b of the brake band and the intermediate layer 300, or between the base layer 30 and the surface protective coating 3, or between the intermediate layer 300 and the base layer 30.
[0059] For the sake of simplicity of disclosure, the brake disc 1 will be described together with the method according to the invention. The brake disc 1 is preferably, but not necessarily, manufactured by the method according to the invention described below.
[0060] According to a first aspect of the invention, a general embodiment of the method according to the invention comprises the following operating steps: a) providing a brake disc comprising a brake band with two opposing braking surfaces 2a, 2b, each brake band defining at least a part of the two main faces of the disc, the brake band being made of grey cast iron or steel; b) depositing a layer of steel containing up to 15% nickel, preferably by a laser deposition technique, such as laser metal deposition or very fast laser material deposition, or a thermal spray deposition technique, or a cold spray deposition technique, to form a base layer 30; c) optionally, a particulate material made of tungsten carbide (WC) or niobium carbide (NbC) or titanium carbide (TiC) or possibly chromium carbide is applied on said base layer 30, for example by HVOF (High-Vol. HVOF (High-Velocity Oxy-Fuel) technology, HVAF (High-Velocity Air Fuel) technology, APS (Atmosphere Plasma Spray) technology, Cold Spray deposition technology, for example KM (Kinetic Metallization) technology, or laser beam deposition technology, for example LMD (Laser Metal Deposition) technology, or by HSLC (High Speed Laser Cladding) technology, or by EHLA (Extremely High Speed Laser Application) technology, or by TSC (Top Speed Cladding) technology, to form a surface protective coating 3 covering at least one of the two braking surfaces of the braking band, for example covering the base layer 30, preferably covering at least the entire surface of one of the two braking surfaces 2a, 2b of the braking band.
[0061] According to a second aspect of the invention, a further general embodiment of the method according to the invention comprises the following operating steps: a) providing a brake disc comprising a brake band with two opposing braking surfaces 2a, 2b, each brake band defining at least a part of the two main faces of the disc, the brake bands being made of grey cast iron or steel; b) depositing a layer of completely nickel-free steel, preferably by a laser deposition technique, such as laser metal deposition or very fast laser material deposition, or thermal spray deposition, or cold spray deposition, to form the base layer 30; c) optionally depositing a particulate material of tungsten carbide (WC) or niobium carbide (NbC) or titanium carbide (TiC) or possibly chromium carbide on said base layer 30; A surface protective coating 3 is formed by a thermal spray deposition technique (e.g., HVOF (High-Velocity Oxy-Fuel) technique, HVAF (High-Velocity Air Fuel) technique, APS (Atmosphere Plasma Spray) technique, or Cold Spray deposition technique), KM (Kinetic Metallization) technique, or laser beam deposition technique (e.g., LMD (Laser Metal Deposition) technique, HSLC (High Speed Laser Cladding) technique, EHLA (Extremely High Speed Laser Application) technique, or TSC (Top Speed Cladding) technique) to cover at least one of the two braking surfaces of the brake band, for example to cover the base layer 30, and preferably to cover at least the entire surface of one of the two braking surfaces 2a, 2b of the brake band.
[0062] According to a third aspect of the invention, a further general embodiment of the method according to the invention comprises the following operating steps: a) providing a brake disc comprising a brake band with two opposing braking surfaces 2a, 2b, each brake band defining at least a part of the two main faces of the disc, the brake band being made of grey cast iron or steel. a1) After step a), depositing on at least one of the two opposing braking surfaces 2a, 2b an intermediate layer 300 made of nickel-free steel. b) After step a1), preferably by a laser deposition technique, such as laser metal deposition or very fast laser material deposition, or thermal spray deposition or cold spray deposition, depositing a layer of completely nickel-free steel to form the base layer 30. c) optionally, spray-depositing on said base layer 30 a particulate material consisting of tungsten carbide (WC) or niobium carbide (NbC) or titanium carbide (TiC) or chromium carbide, for example by HVOF (High Spray Deposition) technology, forming a surface protective coating 3 covering at least one of the two braking surfaces of the brake band, for example covering the base layer 30, preferably covering at least the entire surface of one of the two braking surfaces 2a, 2b of the brake band, by HVOF (High-Velocity Oxy-Fuel) technology, HVAF (High-Velocity Air Fuel) technology, APS (Atmosphere Plasma Spray) technology, cold spray deposition technology, for example KM (Kinetic Metallization) technology, or laser beam deposition technology, for example LMD (Laser Metallization) technology, or HSLC (High Speed Laser Cladding) technology, or EHLA (Extremely High Speed Laser Application) technology, or TSC (Top Speed Cladding) technology.
[0063] According to an advantageous embodiment, step a1) comprises depositing an intermediate layer 300 consisting of nickel-free steel, 10%-15% chromium (Cr), at most 1% silicon (Si), at most 4% manganese (Mn), 0.16%-0.5% carbon (C), preferably 0.16%-0.25% carbon (C) including the extremes, and the balance iron (Fe). According to a further aspect of the invention, a further general implementation of the method according to the invention comprises the following operating steps: a) Providing a brake disc 1, comprising a brake band 2 with two opposing braking surfaces 2a, 2b, each brake band defining at least a part of the two main faces of the disc, the brake band being made of grey cast iron or steel. b) depositing a base layer 30 consisting of nickel-free steel, 10% to 15% chromium (Cr), at most 1% silicon (Si), at most 4% manganese (Mn), 0.16% to 0.5% carbon (C), preferably 0.16% to 0.25% carbon (C), the remainder iron (Fe);
[0064] According to a further aspect of the invention, a general embodiment of the method according to the invention comprises the following operating steps: a) providing a brake disc comprising a brake band with two opposing braking surfaces 2a, 2b, each brake band defining at least a part of the two main faces of the disc, the brake band being made from grey cast iron or steel. a1) after step a), depositing on at least one of the two opposing braking surfaces 2a, 2b an intermediate layer 300 made of nickel-containing steel, preferably according to the characteristics described in the previous paragraphs of the present disclosure. b) After step a1), depositing a layer of completely nickel-free steel, preferably by a laser deposition technique, such as laser metal deposition or ultra-fast laser material deposition, or thermal spray deposition or cold spray deposition, to form the base layer 30. c) optionally, a particulate material made of tungsten carbide (WC) or niobium carbide (NbC) or titanium carbide (TiC) or possibly chromium carbide is deposited on said base layer 30, for example by a thermal spraying technique such as the HVOF (High Spray Deposition) method, the HVOF (High-Velocity Oxy-Fuel) technique, the HVAF (High-Velocity Air Fuel) technique, the APS (Atmosphere Plasma Spray) technique, the Cold Spray deposition technique, for example the KM (Kinetic Metallization) technique, or a laser beam deposition technique, for example the LMD (Laser Metal Deposition) technique, or by the HSLC (High Speed Laser Cladding) technique, or by the EHLA (Extremely High Speed Laser Application) technique, or by the TSC (Top Speed Cladding) technique, to form a surface protective coating 3 covering at least one of the two braking surfaces of the braking band, for example covering the base layer 30, preferably covering at least the entire surface of one of the two braking surfaces 2a, 2b of the braking band.
[0065] Furthermore, in the above-mentioned general implementation variant of the method according to the invention, preferably, the method comprises the further steps described below.
[0066] Preferably, in step c) tungsten carbide (WC) or niobium carbide (NbC) or titanium carbide (TiC) or possibly chromium carbide is dispersed in the metal matrix.
[0067] According to a preferred embodiment, in step c), the particulate material consists of chromium carbide and titanium carbide.
[0068] Advantageously, the brake disc comprises a part suitable for fixing the disc 1 to the vehicle, this part consisting of an annular part 4 arranged at the centre of the disc 1 and concentric with the brake band 2. The fixing part 4 supports a connecting element 5 to the wheel hub (i.e. the bell). The bell may be made integral with the annular fixing part (as shown in the attached figures) or may be made separately and then fixed to the fixing part by suitable connecting elements.
[0069] The annular fastener 4 may be made of the same material as the brake band, i.e. grey cast iron, or of any other suitable material. The bell 5 may also be made of grey cast iron or of any other suitable material. In particular, the entire disc (i.e. brake band, fastener and bell) may be made of grey cast iron.
[0070] Preferably, the brake band 2 is made by casting. Likewise, if the fixing part and / or the bell are made of grey cast iron, these may also be manufactured by casting.
[0071] The annular fixing portion may be made integral with the brake band (as shown in the accompanying figures) or may be made as a separate piece mechanically connected to the brake band.
[0072] The HVOF, HVAF or KM, or LMD or HSLC techniques are three deposition techniques well known to those skilled in the art, so a detailed description is omitted.
[0073] HVOF (High-Velocity Oxygen Fuel) is a powder spray coating technology that uses an atomizer equipped with a mixed combustion chamber and an atomizing nozzle. Oxygen and fuel are fed into the chamber. The hot combustion gases formed at a pressure close to 1 MPa pass through a converging-diverging nozzle, and the powder material reaches hypersonic speed (i.e. higher than MACH1). The powder material to be coated is injected into the hot gas stream, in which it rapidly melts and is accelerated at a speed of 1000 m / s. Upon impact with the coating surface, the molten material is rapidly cooled and forms a very dense and compact structure due to the high kinetic energy impact.
[0074] HVAF (High Velocity Air Fuel) deposition technology is similar to HVOF technology. The difference is that in HVAF technology, air is fed into the combustion chamber instead of oxygen. Therefore, the temperature at hand is lower than in HVOF technology. This allows more control over the thermal transformation of the coating.
[0075] Kinetic Metallization (KM) deposition is a solid-state deposition process in which metal powder is sprayed through a sonic deposition nozzle in two stages, accelerating and triboelectrically charging the metal particles in an inert gas stream. The carrier stream is supplied with thermal energy. In this process, the potential energy of the compressed inert gas stream and the supplied thermal energy are converted into kinetic energy of the powder. Once the particles are accelerated and charged at high speed, they are directed towards the deposition surface. When metal particles impact such a surface at high speed, they undergo a large deformation (about 80% in the direction perpendicular to the impact). This deformation significantly increases the surface area of the particles. As an effect of the impact, an intimate contact is formed between the particles and the deposition surface, which leads to the formation of a metallic bond and the formation of a coating with a very dense and compact structure.
[0076] Advantageously, as an alternative to the three deposition techniques mentioned above that share the fact of being high kinetic energy impact deposition techniques, other techniques can be used that utilize different deposition methods but are capable of producing coatings with a very dense and compact structure.
[0077] The combination of HVOF or HVAF or KM or LMD or HSLC deposition techniques and the chemical components used to form the base layer 30 and the surface protective coating 3 makes it possible both to obtain high bond strength on the underlying material on which they are deposited and to deposit powders with a high carbide content.
[0078] As mentioned above, the base layer 30 and the protective surface coating 3 cover at least one of the two braking surfaces of the braking band.
[0079] In the following, the term "coating" refers to both the whole provided by the base layer 30 and the surface protective coating 3, and in variants not including the surface protective coating 3 but including carbides in the base layer 3, it refers only to the base layer 30.
[0080] Preferably, the disc 1 is provided with a coating 3, 30 covering both braking surfaces 2a, 2b of the braking band 2, as shown in Figures 2 and 3.
[0081] In particular, the coating 3, 30 may cover only the braking band, a single braking surface, or both.
[0082] According to solutions not shown in the attached figures, the coating 3, 30 may extend to other parts of the disc 1, such as the annular fastening part 4 and the bell 5, up to covering the entire surface of the disc 1. In particular, the coating 3, 30 may cover only the fastening part or only the bell, in addition to the brake band. The choice is substantially determined by aesthetic reasons, in order to obtain a uniform colouring and / or finish over the entire disc or over parts of it.
[0083] Advantageously, the deposition of the particulate material for forming the coatings 3, 30 can be carried out in a differentiated manner on the surface of the disk, at least in terms of the thickness of the coating.
[0084] In the braking band area the coating 3, 30 can be of the same thickness on the two opposing braking surfaces. Another solution can also be provided, in which case the coating 3, 30 is made by differentiating a different thickness between the two braking surfaces of the braking band.
[0085] According to one embodiment of the method, step b) of depositing the base layer 30 comprises depositing, by a laser deposition technique, preferably LMD (Laser Metal Deposition) or EHLA (Extremely High Rate Laser Material Deposition), or by a thermal spray deposition technique, or by a cold spray deposition technique, a particulate composition made of steel with a nickel content at most equal to 15%, or at most equal to 7.5%, or at most equal to 5%, or containing no nickel at all.
[0086] In an advantageous embodiment, in step b), the composition in particulate form further comprises a carbide admixed in a proportion not exceeding 50% by weight of the total particulate composition.
[0087] In an advantageous embodiment, in step b), the particulate composition, in addition to the steel, also comprises a metal oxide or a mixture of metal and ceramic material, preferably a mixture of aluminum oxide Al2O3 or a mixture of Al2O3 and an intermetallic matrix Fe-Cr, for example Fe28Cr.
[0088] In an advantageous embodiment, in step b), the composition in the form of particles consists, in addition to the steel, of a metal oxide or a mixture of metal and ceramic material, preferably an aluminum oxide Al2O3, or a mixture of Al2O3 with an intermetallic matrix Fe-Cr, for example Fe28Cr, also including Fe28Cr, and one or more of the carbides selected from the group consisting of tungsten carbide (WC), niobium carbide (NbC), titanium carbide (TiC), chromium carbide.
[0089] It is therefore evident that by means of the above-mentioned variant of the method it is possible to obtain a braking band 2 whose base layer 30 consists of a mixture of the above-mentioned steel and metal oxides or, in another variant, of a mixture of steel, metal oxides and the above-mentioned carbides.
[0090] The preferred variant of the braking band, and also the arrangement sequence of the base layer 30, the intermediate layer 300 and the surface covering layer 3, will be better understood with reference to the attached figures.
[0091] Preferably, step a1) of depositing the intermediate layer 300 comprises depositing a particulate composition consisting of steel having a nickel content of 5%-15% by a laser deposition technique, preferably LMD (Laser Metal Deposition) or EHLA (Extremely High Rate Laser Material Deposition), or by a thermal spray deposition technique, or by a cold spray deposition technique.
[0092] According to an advantageous variant of the method, the method comprises a step e1) of depositing an auxiliary ferrite-nitrocarburized layer between one of the two braking surfaces 2a, 2b of the braking band and the base layer 30 and / or between one of the two braking surfaces 2a, 2b of the braking band and the intermediate layer 300 and / or between the base layer 30 and the protective surface coating 3 and / or between the intermediate layer 300 and the base layer 30.
[0093] According to an advantageous embodiment, the method comprises a step e2) of depositing an auxiliary ferroalumination layer between one of the two braking surfaces 2a, 2b of the braking band and the base layer 30 and / or between one of the two braking surfaces 2a, 2b of the braking band and the intermediate layer 300 and / or between the base layer 30 and the protective surface coating 3 and / or between the intermediate layer 300 and the base layer 30.
[0094] Preferably, the ferroalumination step e2) consists of the following steps: e21) at least partially immersing said brake band 2 in molten aluminium maintained at a predetermined temperature such that the molten aluminium covers at least a predetermined surface area of said brake band 2, said immersion being extended for a predetermined time so as to allow diffusion of aluminium atoms into the surface microstructure of said cast iron or steel with the formation of intermetallic iron-aluminium compounds in the surface layer of said brake band 2, thereby producing a layer of intermetallic iron-aluminium compounds in said predetermined surface area of said brake band 2. e22) Extracting the brake band 2 from the molten aluminum. e23) Removing the aluminium remaining attached to said braking band 2 after extraction to expose said layer of intermetallic iron-aluminium compounds at the surface.
[0095] The layer of intermetallic iron-aluminum compounds exposed at the surface provides the cast iron or steel brake band 2 with high corrosion and wear resistance in said defined surface area.
[0096] Preferably, the intermetallic iron-aluminum compound layer comprises FeAl3 as the predominant phase of the iron-aluminum intermetallic compound.
[0097] According to an advantageous embodiment, the predetermined temperature at which the molten aluminum is maintained is less than or equal to 750°C, preferably between 690°C and 710°C, and even more preferably equal to 700°C.
[0098] According to an advantageous aspect of the method, the predetermined immersion time duration is fixed as a function of the desired thickness of said intermetallic compound layer, said thickness increasing as the immersion time increases, when the temperature of the molten aluminum is the same, said thickness increasing as the immersion time increases, when the temperature of the molten aluminum is the same, preferably said predetermined immersion time is between 5-60 minutes and even more preferably equal to 30 minutes.
[0099] According to an advantageous embodiment, before the immersion step e21), the method comprises a step f) of decarburizing said predetermined surface area of said braking band 2 to a predetermined depth.
[0100] It has been experimentally shown that the presence of carbon in the surface layer of the brake band, which has undergone diffusion of aluminum atoms (induced by aluminization), leads to the formation of iron carbides in addition to intermetallic compounds. The presence of iron carbides creates discontinuities in the intermetallic layer that can induce both corrosion phenomena and cracking. Advantageously, surface decarburization allows the formation of iron carbides to be avoided (or at least significantly reduced) and allows the formation of an intermetallic layer that is more corrosion resistant and less prone to cracking.
[0101] Preferably, in step f), the decarburization of the at least one predetermined surface area is carried out by an electrolytic process.
[0102] More specifically, the electrolytic process is carried out by immersing a predetermined surface area of the braking band in a molten salt bath and applying a potential difference between the bath and the braking band.
[0103] When applying a potential difference, the brake band is connected to the positive electrode (cathode) and the molten salt bath is connected to the negative electrode (anode). Carbon, especially in the form of graphite flakes, is oxidized to carbon dioxide by the transfer of atomic oxygen with electrons released at the anode. Carbon reacts primarily with oxygen and ultimately combines as carbon dioxide.
[0104] The oxidation of the brake band surface induced by the electrolytic process is not limited to the carbon present there, but extends into the cast iron (iron) metallic matrix, causing the formation of a surface film of metal oxide. Reversing the polarity reduces the metal oxide surface film, returning it to its original metallic state.
[0105] Preferably, the electrolytic process described above may include reversing the polarity to return the metal oxide film to its original metallic state after a predetermined period during which the surface of the brake band is connected to a cathode to oxidize the carbon.
[0106] Operationally, the decarburization depth is controlled by adjusting the duration of the electrolysis process, possibly divided into several polarity reversal cycles. By increasing the time of the decarburization step (breaking band oxidation step; cathodic connection), the decarburization depth increases, all other conditions being equal.
[0107] Decarburization can also be achieved by alternative processes to the electrolytic process mentioned above, such as laser or chemical processes.
[0108] However, decarburization by electrolysis is preferred for the following reasons. It is much more efficient and quicker than laser treatment, ensuring more complete and uniform carbon removal in a shorter period of time; Electrolytic treatment is much more efficient (ensuring more complete and uniform carbon removal in a shorter time) than chemical treatments (e.g., treatment with potassium permanganate) and does not leave oxidized areas of the cast iron metal matrix in the treated parts.
[0109] More specifically, it has been observed that the oxidized areas on the cast iron metal matrix reduce the wettability of the molten aluminum to a mush, which adversely affects the anodizing and intermetallic layer characteristics. For these reasons, the electrolytic decarburization process is preferred over the alternative processes listed above.
[0110] As already mentioned, the growth thickness of the intermetallic compound layer is mainly influenced by the temperature of the molten aluminum and the immersion time in the molten aluminum. However, it has been found that an additional factor affecting the thickness of the intermetallic compound layer is the silicon content in the molten aluminum. The higher the weight content of silicon in the molten aluminum, the thinner the intermetallic compound layer, other conditions being equal. Preferably, the silicon content in the molten aluminum is less than 1 weight percent.
[0111] Preferably, the molten aluminum has an impurity content not exceeding 1% by weight. In particular, aluminum with a maximum purity of 99.7% by weight can be used, with the following impurities (in % by weight): Si≦0.30%; Fe≦0.18%; Sr≦0.0010%; Na≦0.0025%; Li≦0.0005%; Ca≦0.0020%; P≦0.0020%; Sn≦0.020%.
[0112] In some cases, it was found that, although the brake band was subjected to decarburization, and as a result, the graphite flakes were removed from the surface layer, where the intermetallic layer was formed, the resulting intermetallic layer continued to contain graphite flakes, as if the graphite flakes had not been removed. Such a phenomenon can be explained by the fact that the dissolution of iron in aluminum is so rapid that the decarburized layer is quickly consumed, as a result of which metallic compounds are formed in the layer below the decarburized layer, i.e. in the layer where the graphite flakes are present.
[0113] In other words, excessive solubility of iron in molten aluminum can negate all or part of the beneficial effects of surface decarburization of the brake band.
[0114] Advantageously, a step b1) of immersion in a molten aluminum bath containing dissolved iron can be carried out in order to slow down the dissolution of iron in the aluminum bath, thereby inhibiting the dissolution of iron in the aluminum, kinetically promoting the formation of FeAl3 and allowing the formation of intermetallic compounds in the decarburized zone.
[0115] Preferably, the content of iron in the solution in the aluminum bath does not exceed 5% by weight, more preferably 3%-5% by weight and quite preferably equal to 4% by weight, to ensure a significant effect of slowing down the dissolution process of the iron of the cast iron in the aluminum.
[0116] For example, an aluminum bath of the following composition (by weight) can be used: Al≦97%; Fe 3-5%; with the following impurities: Si≦0.30%; Fe≦0.18%; Sr≦0.0010%; Na≦0.0025%; Li≦0.0005%; Ca≦0.0020%; P≦0.0020%; Sn≦0.020%.
[0117] It has been experimentally found that a more porous intermetallic layer can be obtained by anodizing using an iron-containing aluminum bath, especially when the iron content is close to the solubility limit. This can be explained by the higher viscosity of the molten aluminum bath containing iron compared to cast iron, which results in a lower wettability.
[0118] Advantageously, said step b1) of immersion is carried out in two sub-steps in order to form a compact, homogeneous and therefore less porous intermetallic layer while avoiding the formation of such a layer below the decarburized layer and the incorporation of graphite flakes present therein. a first substep b11 of immersion in a first bath of molten aluminum substantially free of iron in solution (or at most present as an impurity; for example, the iron content is less than 0.20% by weight) in order to obtain an initial layer of intermetallic iron-aluminum compounds on said predetermined surface area; and a second sub-step b12) of immersion in a second molten aluminum bath containing iron in solution in order to increase said initial layer until a final layer of intermetallic iron-aluminum compound having a predetermined thickness is obtained on said predetermined surface area.
[0119] The immersion time of the braking band in the first bath is shorter than the immersion time of the braking band in the second bath.
[0120] Preferably, the immersion of the braking band in the first bath is as short as possible, but extended for a time sufficient to obtain an initial layer of intermetallic iron-aluminium compounds having a thickness not exceeding 10 μm on the defined surface area. In particular, the immersion time in the first bath is 3-5 minutes when the first bath is at a temperature of about 700° C. The immersion time must be reduced as the bath temperature increases.
[0121] More specifically, the thickness increases as the immersion time increases while the temperature of the second bath is the same, and the thickness increases as the immersion time increases while the temperature of the second bath is the same.
[0122] Advantageously, both the first molten aluminium bath and the second bath have an impurity content not exceeding 1% by weight. In particular, the two molten aluminium baths have a silicon content of less than 1% by weight.
[0123] Preferably, the content of iron in the solution in the second aluminum bath does not exceed 5% by weight (solubility limit of iron in aluminum at 700° C. is equal to 4% by weight; iron-saturated aluminum), more preferably between 3% and 5% by weight, and quite preferably equal to 4% by weight. To ensure a significant effect of slowing down the dissolution process of iron from cast iron into aluminum, the iron content should not be less than 3%.
[0124] Advantageously, both said first bath and said second bath are kept at a temperature below 680°C, preferably not higher than 750°C, more preferably between 690°C and 710°C, and even more preferably equal to 700°C.
[0125] Advantageously, the method may comprise a step of surface pretreatment of the braking band, carried out at least in said predetermined surface area, before said step e21) of immersion. Preferably, said surface pretreatment step consists of lapping, degreasing, sandblasting and / or chemical removal of surface oxides.
[0126] Preferably, the method comprises a step of removing the surface oxide layer from the molten aluminum bath prior to the immersion of said step e21), said step of removing the surface oxide being carried out both when the immersion is carried out in a single bath and when the immersion is carried out in two successive steps in a first and a second bath.
[0127] According to a preferred embodiment of the invention, the step of removing the aluminium remaining attached to said brake band after extraction is carried out in two sub-steps. A first removal sub-step is performed on the brake band that has just been extracted from the molten aluminium to remove any molten aluminium that remains attached to the brake band. A second stripping sub-step is performed on the brake band which has been extracted from the molten aluminum and cooled to remove any solidified residual aluminum remaining after the first stripping sub-step.
[0128] Preferably, the method includes a step of quenching said braking band carried out between said first sub-step of removing and said second sub-step of removing.
[0129] Advantageously, said first sub-step of removal can be carried out by mechanical shaving of the aluminium while it is still liquid.
[0130] Advantageously, said second removal substep may be carried out by chemical removal of the solidified aluminium that has not been mechanically removed.
[0131] Preferably, the chemical removal is carried out by exposing the aluminum to ferric chloride for at least 4 minutes, resulting in the following reaction: Al+FeCl3→AlCl3+Fe
[0132] The chemical removal with ferric chloride must necessarily take place after the solidification of the aluminium: ferric chloride boils at 315° C. and therefore cannot be in contact with the molten aluminium. Preferably, said chemical removal takes place after the quenching step.
[0133] Said step of the method referring to ferroalumination therefore makes it possible to obtain a braking band, and thus a brake disc, with improved wear and corrosion resistance.
[0134] It is worth noting that the intermetallic iron-aluminum compound layer may be composed of multiple intermetallic compounds between iron and aluminum, in particular Fe3Al, FeAl, FeAl2, FeAl3 and Fe2Al5. The predominant intermetallic phase is the thermodynamically stable FeAl3.
[0135] According to one embodiment, the method comprises depositing an auxiliary ferrite-nitrocarburized layer and an auxiliary ferroaluminate layer between one of the two braking surfaces 2a, 2b of the braking band and the base layer 30, and / or between one of the two braking surfaces 2a, 2b of the braking band and the intermediate layer 300, and / or between the base layer 30 and the protective surface coating 3, and / or between the intermediate layer 300 and the base layer 30.
[0136] As can be seen from the above description, the brake disc according to the invention makes it possible to overcome the drawbacks introduced in the prior art.
[0137] Due to the combination of a base layer of steel with a reduced nickel content or completely nickel-free, and the cast iron band, the brake disc 1 according to the invention is substantially free from the tendency to generate and release nickel particles during use.
[0138] Furthermore, according to a particularly advantageous variant, the addition of a surface protective coating 3 containing or coated with carbides improves the wear resistance properties and can also compensate for the deficiency of nickel in the steel of the base layer and provide an appropriate increased mechanical strength.
[0139] In a particularly advantageous embodiment, a base layer 30 consisting of a completely nickel-free steel and 10%-15% chromium (Cr), at most 1% silicon (Si), at most 4% manganese (Mn), 0.16%-0.5% carbon (C), preferably 0.16%-0.25% carbon (C) and the balance iron (Fe) allows the production of a nickel-free martensitic steel that is less brittle during high temperature use and at the same time has a sufficient anticorrosive coating. Moreover, this advantageous aspect is synergistically combined with the possibility of reducing the proportion of carbides in the steel, thus reducing the resources required for production while maintaining an adequate coating hardness.
[0140] Advantageously, the preferably nickel-free base layer 30 also performs a mechanical "cushion" function (wear protection) for the protective overcoat 3. Indeed, the base layer 30 exhibits an elastic behavior that at least partially damps the stresses exerted on the disk during use. The base layer 30 therefore acts as a kind of damper or cushion between the disk and the protective overcoat 3. This prevents a direct transmission of stresses between the two parts and also reduces the risk of cracks in the protective overcoat 3.
Claims
1. A brake disc (1) for a disc brake, comprising a brake band (2) with two opposing braking surfaces (2a, 2b), each of which at least partially defines one of the two main surfaces of the brake disc (1), the brake band (2) being made of grey cast iron or steel, The brake disc (1) comprises a base layer (30) covering at least one of the two braking surfaces (2a, 2b) of the brake band (2), The base layer (30) is made of steel that is completely nickel-free and free of impurities, The steel of the base layer (30) is composed of 10% to 15% chromium (Cr), 1% silicon (Si) at most, 4% manganese (Mn) at most, 0.16% to 0.5% carbon (C) including extremes, and the balance iron (Fe), a brake disc (1) for a disc brake.
2. Brake disc (1) for disc brakes according to claim 1, wherein the base layer (30) further comprises one or more carbides contained in nickel-free steel.
3. 3. The brake disc for a disc brake according to claim 2, wherein the one or more carbides contained in the base layer include at least one carbide selected from the group consisting of tungsten carbide (WC), chromium carbide (CrC), niobium carbide (NbC) and titanium carbide (TiC).
4. A brake disc (1) for a disc brake according to any one of claims 1 to 3, characterized in that an intermediate layer (300) of nickel-free steel is interposed between the base layer (30) and at least one of the two braking surfaces (2a, 2b) of the brake band (2).
5. 5. A brake disc (1) for a disc brake according to claim 4, wherein the intermediate layer (300) comprises nickel-free steel consisting of 10% to 15% chromium (Cr), maximum 1% silicon (Si), maximum 4% manganese (Mn), 0.16% to 0.5% carbon (C) and the balance iron (Fe).
6. 4. A brake disc (1) for a disc brake according to claim 1, wherein an intermediate layer (300) of nickel-containing steel is interposed between the base layer (30) and at least one of the two braking surfaces (2a, 2b) of the braking band (2).
7. Brake disc (1) for disc brakes according to claim 6, wherein said intermediate layer (300) comprises steel with a nickel content of at most or equal to 15%.
8. Brake disc (1) for a disc brake according to claim 7, wherein said intermediate layer (300) comprises steel having a nickel content maximum equal to 7.5%.
9. a surface protective coating (3) covering the base layer (30) at least on one side of the two braking surfaces (2a, 2b) of the brake band; the surface protective coating (3) is arranged on the side of the base layer (30) that does not face one of the two braking surfaces (2a, 2b); The surface protective coating (3) is For example, thermal spray coating technologies such as HVOF (High Velocity Oxy-Fuel) technology, HVAF (High Velocity Air Fuel) technology, and APS (Atmosphere Plasma Spray) technology, For example, the cold spray deposition technology of KM (Kinetic Metallization) technology, For example, a deposition technique such as LMD (Laser Metal Deposition) technology, HSLC (High Speed Laser Cladding) technology, EHLA (Extreme High Speed Laser Application) technology, or TSC (Top Speed Cladding) technology. A brake disc (1) for a disc brake according to any one of claims 1 to 8, which is composed of one or more carbides in the form of particles deposited by
10. A brake disc (1) for a disc brake according to claim 7, wherein the particulate carbide or carbides consist of tungsten carbide (WC) or chromium carbide (CrC) or niobium carbide (NbC) or titanium carbide (TiC).
11. Brake disc (1) for disc brakes according to any one of claims 1 to 10, wherein the percentage of chromium in the base layer (30) is between 11% and 14%, extreme values included.
12. A brake disk (1) for a disk brake according to any one of claims 1 to 11, characterized in that an auxiliary ferrite-nitrocarburized layer or an auxiliary ferroaluminate layer is interposed between one of the two braking surfaces (2a, 2b) of the brake band and the base layer (30), and / or between one of the two braking surfaces (2a, 2b) of the brake band and the intermediate layer (300), and / or between the base layer (30) and the surface protective coating (3), and / or between the intermediate layer (300) and the base layer (30).
13. a) providing a brake disc (1) comprising a brake band (2) with two opposing braking surfaces (2a, 2b) each defining at least a portion of the two main surfaces of the brake disc (1), said brake band (2) being made of grey cast iron or steel; b) A method for manufacturing a brake disc, depositing a base layer (30) made of steel which is completely nickel-free, free of impurities, and which contains 10% to 15% chromium (Cr), maximum 1% silicon (Si), maximum 4% manganese (Mn), 0.16% to 0.5% carbon (C) and the remainder iron (Fe).
14. 14. Method for manufacturing a brake disc according to claim 13, characterized in that step b) of depositing the base layer (30) provides for depositing a particulate composition made of nickel-free steel by a laser deposition technique, preferably by laser metal deposition or very high speed laser material deposition, or by a thermal spray deposition technique or by a cold spray deposition technique.
15. A particulate material made of tungsten carbide (WC), niobium carbide (NbC), titanium carbide (TiC), or chromium carbide is deposited on the base layer (30); For example, a thermal spray deposition technology such as HVOF (High-Velocity Oxy-Fuel) technology, HVAF (High-Velocity Air Fuel) technology, APS (Atmosphere Plasma Spray) technology, or cold spray deposition technology; For example, by deposition using the laser beam deposition technique, the LMD (laser metal deposition) technique, the HSLC (high speed laser cladding) technique, the EHLA (extremely high speed laser application) technique, or the TSC (top speed cladding) technique, the KM (Kinetic Metalation) technique, 15. The method according to claim 13 or 14, comprising a step c) of forming a protective surface coating (3) covering said base layer (30), preferably at least the entire surface of one of said two opposing braking surfaces (2a, 2b) of said braking band (2).
16. After step a) and before step b), a1) depositing on at least one of the two opposing braking surfaces (2a, 2b) an intermediate layer (300) which is nickel-free and consists, to the exclusion of impurities, of 10% to 15% chromium (Cr), at most 1% silicon (Si), at most 4% manganese (Mn), 0.16% to 0.5% carbon (C) and the balance iron (Fe).